2020
DOI: 10.3390/jcm9092741
|View full text |Cite
|
Sign up to set email alerts
|

Association between Left Atrial Deformation and Brain Involvement in Patients with Anderson-Fabry Disease at Diagnosis

Abstract: Background: Anderson-Fabry disease (AFD) can induce both central nervous system white matter lesions (WMLs) and cardiac abnormalities including left atrial (LA) dysfunction. We sought to evaluate the possible interrelations of LA structure and function impairment with the presence of WMLs in AFD patients. Methods 22 AFD patients and 22 controls, matched for age and sex, underwent an echo-Doppler exam including quantification of peak atrial longitudinal strain (PALS). AFD patients underwent also a 3-T brain mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Left atrial (LA) systolic and early diastolic strain rate were found preferentially reduced in patients with LVH, but LA systolic strain was decreased even before LVH [ 96 ]. Peak atrial longitudinal strain was inversely associated to Fazekas score of brain white matter lesions, even after adjusting for LV mass index [ 97 ]. Atrial dilation is associated to the occurrence of atrial fibrillation [ 98 ], which also contributes to heart failure.…”
Section: Cardiac Manifestations Of Fdmentioning
confidence: 99%
“…Left atrial (LA) systolic and early diastolic strain rate were found preferentially reduced in patients with LVH, but LA systolic strain was decreased even before LVH [ 96 ]. Peak atrial longitudinal strain was inversely associated to Fazekas score of brain white matter lesions, even after adjusting for LV mass index [ 97 ]. Atrial dilation is associated to the occurrence of atrial fibrillation [ 98 ], which also contributes to heart failure.…”
Section: Cardiac Manifestations Of Fdmentioning
confidence: 99%
“…In this context, LALS might be a sensitive marker of preclinical insult, translating diastolic impairment and a rise in filling pressures [ 33 , 34 ], as shown in children [ 27 , 28 ]. Atrial strain has emerged as a sensitive tool in early detection of subtle or early changes in the setting of various cardiac conditions such as atrial fibrillation, valvulopathies, systemic diseases, heart failure with preserved ejection fraction and diastolic dysfunction [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. LALS changes usually precede other structural variations such as left atrial volume increase and systolic dysfunction in heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Left atrial longitudinal strain (LALS) has recently emerged as a useful tool, generating independent added value in different scenarios such as valvulopathies, atrial fibrillation, heart failure and systemic diseases [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. It has also been postulated as a means for evaluating diastolic function and left ventricular filling pressures [ 11 , 12 , 13 , 14 ], reported to be altered in acute cellular rejection (ACR) episodes in heart transplant (HTx) recipients [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were notable because LA dilatation and impaired LA function correlated with the quantity of white matter lesions on cerebral MRI and high Fazekas score. The exact aetiology of white matter lesions in FD is uncertain but these data raise the possibility that altered atrial size and function may predispose the FD patient to atrial arrhythmia and stroke, in addition to simultaneous sphingolipid accumulation in the heart and brain [67].…”
Section: Arrhythmiamentioning
confidence: 99%